Developing class scheduler system / Mohamed Imran Mohamed Ariff - Mohamed Ariff, Mohamed Imran (2006)
This research considers a solution to the Class Scheduling problem. The class scheduling problems involves scheduling a number of situation, each consisting of a class of students, a lecturer/teacher, a subject and a room, and lastly with a fixed number of time slots. A basic solution is presented in this research. The algorithm used in this research is the truth table approach. This algorithm has been proven to come out with faster solutions that the standard sequential time-tabling algorithms.